Reading the Old Testament as Christian scripture: a literary, canonical, and theological survey - Gignilliat, Mark S. (Reading Christian scripture, 2025)
"This survey textbook presents the Old Testament and major Old Testament topics effectively for contemporary undergraduate students"--